The Production and Characterisation of a Panel of Ten Murine Monoclonal Antibodies to Human Procoagulant Factor VIII - Griffin, B D; Micklem, L R; McCann, M C; James, K; Pepper, D S (Thrombosis and Haemostasis, 1986)
A panel of 10 murine monoclonal antibodies to procoagulant FVIII has been developed from the fusion of a single spleen. Balb/c mice were injected with a purified preparation of FVIII: Ag, and antibody production in sera and hybrid culture supernatants was monitored using a specific radiometric screening assay. The antibodies all inhibit FVIII clotting activity in normal plasma, and when immobilised on agarose retain their ability to recognise and bind the FVIII procoagulant protein. Studies on protein A-purified immunoglobulins demonstrate a range of properties within the panel of antibodies with regard to species crossreactivity, clotting inhibition and immunoadsorption. The panel of antibodies has been used to screen heat-treated FVIII concentrates for the occurrence of heat-induced neoantigens.
Keywords: Factor VIII; Monoclonal antibodies